BEAM FORMING OF ADAPTIVE SMART ANTENNA ARRAYS USING COMBINED ALGORITHM (International Journal of Engineering Sciences & Management Research, 2017)
Beam forming is done for antenna arrays using combined algorithms like SMI with LMS and its variants. Then a comparative study of beam forming techniques using combined algorithms like sample matrix inversion with least mean square (SMI-LMS), simple matrix inversion with recursive least square (SMI-RLS) and least mean square with recursive least square (LMS-RLS) algorithm is presented. The performances of the algorithms are compared on the basis of side lobe level, null depth and square error estimation.